Nonstationnary teleconnexions of Atlantic low-frequency oscillations and the regional climates of NW Europe (1700-2010) and West African Sahel (1900-2010) - (:unkn) unknown (My University, 2013)
Since the industrial revolution, an anthropogenic forcing occurs over all time-scales of natural variability. This change resulted in significant variations of climate on the regional scale. Therefore, based on spectral analysis, this dissertation revisits the question of the spatiotemporal non-stationnarity of teleconnections between the global climatic variability in the Atlantic and the regional climates of NW Europe and West-Africa. The study of long-term climatic records back to the pre-industrial period reveals similar trends in temperatures of England and Northern France, contrary to trends of rainfalls. Multi- and interdecadal variabilities display several periods of enhanced amplitude for both temperature and rainfall that may be related to large-scale climate control. On these scales, the relationship between the Atlantic Multidecadal Oscillation (AMO) and temperatures is marked by phase changes over the 19th century. For rainfall, coherence with AMO is observed for scales at around 30-60-year, whereas coherence with the North Atlantic Oscillation (NAO) is detected on 50-80-year and interdecadal 16-23-year scales. However, NAO/rainfall teleconnections are highly unstable due to spatial fluctuations of NAO patterns. After the Little Ice Age, the NAO pattern seems shifted south-westwards in winter and spring. Moreover, the results of an analysis of North Atlantic sea-level pressure (SLPs) at these co-oscillation time scales highlight not only NAO regimes, but also other patterns explaining a non-negligible amount of variance. Over West-Africa, zonal contrasts are identified through a study of time-evolutions of Sahel rainfall variability. These patterns are more pronounced at quasi-decadal scale. The teleconnections with Atlantic sea-surface temperatures (SSTs), which depend on time-scales, also show east-west contrasts. During the 20th century, a synchronous Sahel rainfall teleconnection with North Atlantic and Tropical South Atlantic SSTs is
Keywords: African Research